PENGARUH FAKTOR FUNDAMENTAL TERHADAP RETURN SAHAM PADA PERUSAHAAN LQ-45 DI BURSA EFEK INDONESIA - Nanan Karyadi; Rita Rita (Institut Teknologi dan Bisnis Swadharma, 2021)
This study aims to determine the effect of Earning Per Share, Price Earning Ratio, Return On Equity, Firm Size and Earning Growth both partially and simultaneously on Stock Returns on LQ-45 Companies property, real estate and construction sector listed on the Indonesia Stock Exchange with a research period during 2014-2018. This type of research data is quantitative data. The sampling method used was purposive sampling method, so that 8 sample companies from a population of 14 companies or 40 finansial statement were obtained for 5 years of observation (2014-2018). The data analysis technique used is multiple regression analysis, wish the help SPSS Program . The data analysis process is done first is descriptive statistics, the classic assumption test, multiple linear regression analysis and then hypothesis testing. The results of this study partially show that Earnings Per Share, Price Earning Rasio, Firm Size and Earning Growth do not significantly influence Stock Returns, while Return On Equity have a significant effect on Stock Returns. The F test results of the study show that Earning Per Share, Price Earning Rasio, Return On Equity, Firm Size, and Earning Growth simultaneously have a significant effect on Stock Returns. The value of the coefficient of determination is 31% indicates that 69% of Stock Return are influenced by other variables not examined in this study. Based on the results of this study prove that investors use the Return On Equity data contained in the issuer's financial statements as a health analysis tool for a stock to obtain a decent return from a stock investment.